TOWARDS A JUDICIOUS PRESERVATION AND UTILISATION OF WATER FOR A BETTER NIGERIA - Muhammad, Usman Jimoh; Dukuly, Omar Abdallah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
Water is a fundamental resource vital for sustaining life and supporting diverse activities such as agriculture, industry, and electricity generation. Despite its abundance, Nigeria faces significant challenges in water preservation and utilization due to factors such as public apathy toward government resources, insufficient maintenance of water infrastructure, industrial pollution, and inadequate collaboration between the government and private sectors. This study, grounded in Islamic teachings, aims to explore effective strategies for addressing these challenges while highlighting the moral and ethical imperatives for responsible water management. The research adopts a descriptive and literary methodology, drawing insights from relevant texts, journals, and online resources. Islamic principles of accountability, collective responsibility, and sustainability provide the framework for analyzing and proposing solutions. Findings reveal that poor sanitation, insufficient investment in dam infrastructure, and lack of administrative commitment exacerbate water-related issues in Nigeria. Moreover, public awareness and adherence to Islamic values, such as avoiding wastage and prioritizing communal welfare, are essential for ensuring long-term solutions. The study introduces a novel approach by integrating Islamic teachings with contemporary water management practices, emphasizing the role of ethical leadership and communal collaboration. It concludes that fostering private-sector engagement, expanding water infrastructure, and cultivating public awareness through Islamic values can significantly enhance water preservation efforts. These strategies, when implemented effectively, not only address Nigeria’s pressing water challenges but also contribute to sustainable development and societal well-being.